Pursuing Autonomy through Dialogue - Davies, Huw (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2016)
In the Self-Access Learning Center (SALC) at a university in Japan, language learners create and implement individual learning plans. Strategies to facilitate reflective dialogue are used by learning advisors to encourage these learners to pursue their language goals and become increasingly less reliant on direction from their teachers. In this paper, a definition for autonomy is given, and the teaching setting is introduced, giving an overview of the SALC and outlining the ways learners use it, drawing on examples of learners at different stages on their journey to autonomy. After looking at theory and practical applications, this paper demonstrates that guiding learners through dialogue is an appropriate way to challenge meanings and raise consciousness, and move learners towards managing their own language learning.